Pengaruh Penambahan Madu Pada Proses Pengenceran Sperma Terhadap Daya Tetas Telur Ikan Lele (Clarias sp) - Meriyanti Ngabito; Sartika Rahim (Gorontalo Fisheries Journal, 2018)
The objective of this study was to evaluate the influence of honey addition on sperm dillution process to eggs hatchability of catfish (Clarias sp.) in Gorontalo Fish Seed Centre. This study has been using completely randomized design with 4 threatments and 3 replications each of them. Treatment A: 0 ml; B: 0.70 ml; C: 0.75 ml; and D: 80 ml each of them was in 100 ml; 99.30 ml; 99.25 ml and 99.20 ml solution of NaCl. The results of this study showed that the highest of larvae survival was on treatment D (76,67%), followed by treatment C (71,11%) and B (65,56%), while the lowest was treatment A (61,11% ). The parameter of water quality which is measured were DO was 3,8 ppm , the temperature was 24,5 0C and pH was 6,67 . So it can be concluded that honey supplementation in sperm dilution has affect to the eggs hatchability and the growth of catfish larvae (Clarias sp). Keywords :  Addition of Honey, Sperm Dilution, Hatching Egg, Catfish   (Clarias sp)